Prefrontal cortex neural activity predicts reduction of non-suicidal self-injury in adolescents with major depressive disorder: An event related potential study - Liu, Huishan; Wen, Yujiao; Liang, Xiumei; Xu, Yifan; Qiao, Dan; Yang, Chunxia; Han, Min; Li, Hong; Ren, Tian; Zhang, Xuemin; Li, Gaizhi; Liu, Zhifen (Frontiers in Neuroscience, 2022)
Background Non-suicidal self-injury (NSSI) is common in adolescent MDD, which is also a risk factor for suicide. However, there is few research on biomarkers and predictors about treatment response of NSSI. The purpose of this study was to find the difference of P300 between adolescent MDD with NSSI and healthy controls, and to explore whether the baseline electrophysiological level can predict the change of NSSI after treatment. Methods We collected 62 first-episode drug-naïve MDD adolescents with NSSI (MDD with NSSI group) and 44 healthy controls (HC group). The demographic data, HAMD score, self-injury frequency and electrophysiological level of NSSI group and HC group were collected. The HAMD score, frequency of NSSI in was also collected after 8 weeks of antidepressant treatment. Results Compared to HC, the latency of the N2, P3a, and P3b components were significantly prolonged, whereas the amplitude of P3a and P3b were decreased in the MDD with NSSI group (P < 0.001). The frequency of self-injury decreased significantly after treatment (P < 0.001). Regression analysis showed that the amplitudes of P3b had a significant positive predictive effect on the rate of change of NSSI frequency after 8 weeks. Conclusion P3b at baseline can be used as potential predictor for the reduction of NSSI in adolescent MDD.